A long arid interlude in the Indian summer monsoon during ∼4, 350 to 3, 450 cal. yr BP contemporaneous to displacement of the Indus valley civilization. (20th July 2018) - Dutt, Som; Gupta, Anil K.; Wünnemann, Bernd; Yan, Dada
Abstract: Climatic variability played a pivotal role in the development of human societies and stability of civilizations in the past. To constrain the causes that drove displacement and deurbanization of the Indus Valley civilization, we present a 4500 yr old proxy record from the Tso Moriri Lake, northwestern (NW) Himalaya. The record indicates an interval of warm and wet climatic conditions from 4500 to 4350 calibrated years before Present (cal. yr BP) with a trend toward deteriorating climate, culminating in a pronounced, long cold and arid phase from∼4350 to 3450 cal. yr BP in the region. The Indian summer monsoon (ISM) weakened during this long arid phase depleting the water resources in the area of the Indus Valley settlements that likely have triggered the gradual abandonment of the Harappan cities. This long interval of ISM weakening and thus aridity in South Asia was driven by enhanced El Niño intensity and frequency.